1992
DOI: 10.1016/0014-5793(92)80820-7
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular cloning and expression of the human melanocyte stimulating hormone receptor cDNA

Abstract: Melanoeytes and melanoma cells are known to possess receptors for melanoeyte stimulating hormone (MSH). A eDNA clone, designated l ID, has b~.~n isolated from human melanoma cells and encodes a MSH receptor. The cloned eDNA encodes a 317 amino acid protein with transmembrane topography characteristics of a G-protein.coupled receptor, bat it does not show striking similarity to already pablish~ sequences of other G-protein-coupl~ receptors. When 11D eDNA is expressed in COS-7 cells, it binds an Z~l-labelled MSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
449
1
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(460 citation statements)
references
References 20 publications
6
449
1
4
Order By: Relevance
“…In this light, the difference in the side chain conformations of the Trp residue of MT-II (gauche-(−), χ 1 = −78°) and PG-951 (trans, χ 1 = −177°) may be responsible for the hMC3R selectivity observed for PG-951. Compound 10 (PG-952), with D-Phe 4 and D-Nal(2′) 7 residues, was found to be a weak partial agonist at the hMC3R (EC 50 = 55 nM), and an antagonist at hMC4 and hMC5 receptors with a low selectivity (hMC4/hMC5 = 14). Finally, since previously, we demonstrated that inserting a D-Nal(2′) residue in 9 position makes it possible to modulate the activity on hMC5R [25], we synthesized two analogues in which we replaced the position 4 with a D-Phe and in position 9, the Trp with a D-Nal(2′).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this light, the difference in the side chain conformations of the Trp residue of MT-II (gauche-(−), χ 1 = −78°) and PG-951 (trans, χ 1 = −177°) may be responsible for the hMC3R selectivity observed for PG-951. Compound 10 (PG-952), with D-Phe 4 and D-Nal(2′) 7 residues, was found to be a weak partial agonist at the hMC3R (EC 50 = 55 nM), and an antagonist at hMC4 and hMC5 receptors with a low selectivity (hMC4/hMC5 = 14). Finally, since previously, we demonstrated that inserting a D-Nal(2′) residue in 9 position makes it possible to modulate the activity on hMC5R [25], we synthesized two analogues in which we replaced the position 4 with a D-Phe and in position 9, the Trp with a D-Nal(2′).…”
Section: Resultsmentioning
confidence: 99%
“…There are five known melanocortin receptor (MCR) subtypes, all of which belong to the family of seven transmembrane G-protein coupled receptors (GPCRs), and whose activation is linked to the generation of intracellular cAMP [3,7,8,12,[14][15][16]22,31,34,38]. Importantly, the interaction of the melanocortin peptides with their receptors can be modified by two endogenous protein antagonists, agouti, and agouti-related protein, which are the products of two distinct genes [33,35].…”
Section: Introductionmentioning
confidence: 99%
“…The Y152X variant and the previously described variants, R151C and R142H, occur in the second intracellular region of the protein, which has been found to contain two sequences for cAMP-dependent protein kinase recognition: from amino acid 142 to 145 and from 151 to 156. Additionally, one other such region is located in the COOH-terminal region (amino acids 306 to 308) (Chhajlani and Wikberg, 1992). The three variants therefore may lead to the production of a protein without sufficient function for signalling cAMP.…”
Section: Resultsmentioning
confidence: 99%
“…To date, five melanocortin receptor (MC-R) subtypes have been identified [3,[7][8][9][12][13][14][15][24][25][26]30]. Three of these, MC3-R, MC4-R and MC~-R are expressed in the nervous system.…”
Section: Introductionmentioning
confidence: 99%